+0  
 
0
381
1
avatar

(6j^-2)^-3

Guest Dec 18, 2014

Best Answer 

 #1
avatar+93644 
+5

$$\\(6j^{-2})^{-3}\\
=6^{-3}\;\;j^{-2*-3}\\\\
=\frac{6^{-3}\;\;j^{6}}{1}\\\\
=\frac{j^{6}}{6^3}\\\\
=\frac{j^{6}}{216}\\\\
$Now if j is an ordinary pronumeral then the question is finished$\\
$but if j is the imaginary number $ \sqrt{-1} \qquad then\\\\
(\sqrt{-1})^6=((\sqrt{-1})^2)^3=(-1)^3=-1\\\\
$ so the final answer would be $
\frac{-1}{216}$$

Melody  Dec 18, 2014
 #1
avatar+93644 
+5
Best Answer

$$\\(6j^{-2})^{-3}\\
=6^{-3}\;\;j^{-2*-3}\\\\
=\frac{6^{-3}\;\;j^{6}}{1}\\\\
=\frac{j^{6}}{6^3}\\\\
=\frac{j^{6}}{216}\\\\
$Now if j is an ordinary pronumeral then the question is finished$\\
$but if j is the imaginary number $ \sqrt{-1} \qquad then\\\\
(\sqrt{-1})^6=((\sqrt{-1})^2)^3=(-1)^3=-1\\\\
$ so the final answer would be $
\frac{-1}{216}$$

Melody  Dec 18, 2014

46 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.